Statewide Profile of Abuse of Older Women and the Criminal Justice Response in Rhode Island, 2002 - Klein, Andrew ([Verlag nicht ermittelbar], 2008)
This study examined the often overlooked and under reported issue of elder abuse. The research focused on female victims of domestic abuse over 50 years of age. The data were also compared to similar data on women under the age of 50. The data were collected in Rhode Island for several reasons, including the state's relatively broad definition of domestic violence and the large number of reports. Researchers examined every domestic violence report made to state and local law enforcement across Rhode Island in 2002 involving women victims 50 years of age and older. These reports include every incident, whether or not police ultimately arrested the alleged suspect, that meets the statutory definition of "domestic violence." The source of the report information was the Domestic Violence and Sexual Assault Reporting Form (DV/SA). Data were also collected about the past criminal activity of the suspects and any charges made after the study incident(s) occurred. The data were found in the Rhode Island Courts' central repository called CourtConnect. The purpose of the study was to better understand the characteristics of the victims and their abusers, the circumstances of the incidences of abuse, and the police response to the reports of domestic abuse. Data collected consisted of independent variables which are organized into conceptual clusters including those relating to victim characteristics, abuser characteristics, the nature of the incident, and the state's response to the incident. The victim characteristics included demographics and abuse history, if any. Abuser characteristics included demographics and criminal history. Incident characteristics described the abuse incidence in detail. Criminal justice response variables outlined how police and courts responded and reacted to the abuse. There were two dependent outcome variables in this study consisting of re-victimization and re-abuse. The data were analyzed using descriptive statistics, bivariate relationships, and multiple logistic regression. This study primarily focused on the response of the criminal justice system to elder abuse, the effect of age of victim, and re-abuse and re-victimization in order to gain a clearer picture into the realities of domestic abuse of elderly women.